RIS Assisted UAV for Weather-Dependent Satellite Terrestrial Integrated Network With Hybrid FSO/RF Systems - Xin Li; Yongjun Li; Xinkang Song; Long Shao; Hai Li (IEEE Photonics Journal)
In this paper, we investigate the performance of hybrid free-space optical (FSO) and radio frequency (RF) relay systems in satellite terrestrial integrated network where the effect of weather conditions is taking into consideration. Specifically, we design three different relay schemes in different weather conditions based on high-altitude platform station (HAPS) and reconfigurable intelligent surface (RIS) assisted unmanned aerial vehicle (UAV). The RF link is modeled by shadowed Rician model while the FSO link is assumed to follow the Gamma-Gamma distribution in the presence of path loss, pointing errors and angle-of-arrival (AOA) fluctuations where it operates under either intensity modulation with direct detection (IM/DD) or heterodyne detection (HD). The performance of our proposed scheme is evaluated in terms of outage probability, average bit-error rate (BER) and ergodic capacity in the form of bivariate Fox's H function and bivariate Meijer's G function. Moreover, asymptotic results and diversity order for the outage and average BER at high signal-to-noise ratio (SNR) regime are also obtained to get more insights. Finally, numerical results and comparison scheme are provided to verify the accuracy and superiority of our scheme.